Moments of hierarchy : constructing social stratification by means of language, food, space and the body in Pohnpei, Micronesia. - Keating, Elizabeth (American Antropological Association, 2000)
In this paper I examine relationships between multiple semiotic modes used to construct hierarchy, and I show the importance of going beyond our traditional notion of language to look at how social actors employ a range of semiotic resources in organizing and interpreting social relations. Using examples from Pohnpei, Micronesia, I show how notions of superior and inferior are compounded through several sign systemsÑspatial relations, food sharing, the body, and language. These systems act oppositionally as well as cooperatively to produce situated ideas of social inequality, ideas built out of disequilibrium of bodies in space, of referents in language, and distribution of resources, as well as contradictions in the interactions of these signs. The compounding of signs not only recruits multiple sensory modes and perspectives in the exposition of hierarchical relations, but entails a notion of the contradictory nature of status relations. Using examples from a Pohnpeian feast, I explore the creative interplay of sign systems in the construction of "moments" of hierarchy in a large, public setting and discuss how through the practice of title-giving, which virtually every adult member of the society participates in, a particular idea of social inequality, built out of multiple sign systems, is mapped onto each body.